Pengaruh Pupuk Kandang dengan Penambahan Mikrob Pelarut Fosfat terhadap Pertumbuhan dan Hasil Kopi Robusta - Sobari, Iing; Pranowo, Dibyo; Wardiana, Edi (Jurnal Tanaman Industri dan Penyegar, 2018)
Farmyard manure and biofertilizer is able to substitute chemical fertilizers in improving the plants growth and production. The manure acts as the energy source for soil microbes, while biofertilizer with phosphate solubilizing microbes (PSM) can increase phosphate (P) availability for plants. The research aimed to investigate the effect of farmyard manure added with PSM on growth and yield of 5 Robusta coffee clones, conducted at Pakuwon Experimental Station, Indonesian Industrial and Beverage Crops Research Institute (IIBCRI), Sukabumi, from January 2014 to June 2017. A split plot design was used with 3 replications. The main plot factors were 5 Robusta coffee clones (BP 308, SA 237, BP 42, BP 358, and BGN 371), whereas the subplot factors were types of fertilizers (chicken, sheep, and cow manure added with PMS), and NPK fertilizers as control. Variables observed were components of vegetative growth, percentage of flowering plants, and weight of fresh berries. The results showed that 5 Robusta coffee clones used exhibited similar responses to the PMS-added farmyard manure application. Chicken manure added with PMS enhanced P-available and improved vegetative growth of coffee plants better than other farmyard manure, similar with the effect of NPK fertilizers. Up to 4 years old plants, the PM-added farmyard manure application did not affect the weight of fresh berries.